THE ROLE OF ESP IN INTERNATIONAL BUSINESS AND NEGOTIATIONS THE CONTRIBUTION OF PRIVATE UNIVERSITIES - Barotov Nurjaxon; Maftuna Nurova (TADQIQOTLAR, 2025)
Annotation:  In  today's  world,  speaking  English  fluently  is  essential  for conducting business with people from various countries. English for Specific Purposes (ESP)  teaches  businesspeople  how  to  speak  the  appropriate  English  for  their  jobs. Private  universities  play  an  essential  role  in  teaching  business  people  this  style  of English. They provide specialized classes that educate the language abilities required for business. These private institutions provide students with the tools they need to converse effectively with people from various countries. This is beneficial for firms looking  to  acquire  and  sell  goods,  as  well  as  collaborate  with  enterprises  in  other countries. When business professionals speak English fluently, it benefits the country's economy, trade, and international relations. Private universities promote international business by offering appropriate skills.